Gårds- og kirkestruktur på Island fram til ca. 1200 - Sigurðsson, Jón Viðar (Hikuin, 2000)
The farm and church structure in Island until c. 1200 By Jón Viðar Sigurðsson Scholars generally agree that the settlement of Iceland was initiated during the second half of the ninth century. A process of adaptation and the subdivision of farms into smaller holdings followed the colonisation of the island, a process that continued into the eleventh century. From the eleventh century onwards, Icelandic settlement has been characterised by stability and continuity. At an early stage, between the early-tenth and the early-eleventh century, Icelandic settlements were divided into social and territorial units called hreppir (singular, hreppr). These hreppir may very well have been modelled on European medieval guilds. The main function of the hreppr was to mutually secure its members economically. Some decades after the introduction of tithe, the bishops started founding parishes. It was natural that the borders of the hreppir were used as the borders of the parishes, even if there were two or more churches within the boundaries of one hreppr.